Low-Cost AWG-Based Fundamental Frequency Mode-Locked Semiconductor Laser for Multichannel Synchronous Ultrashort Pulse Generation - Songtao Liu; Xilin Zhang; Wei Wang; Lingjuan Zhao; Qiang Kan; Dan Lu; Ruikang Zhang; Chen Ji (IEEE Photonics Journal)
We report a low-cost arrayed waveguide grating (AWG) based mode-locked semiconductor laser designed for multichannel synchronous ultrashort pulse generation. Both the fabrication process and chip characterization results are discussed in detail. By deploying a bundle active–passive photonic integration technique, only one regrowth step is required to monolithically integrate a semiconductor optical amplifier array, an AWG, and a common saturable absorber on a single InP substrate. Combined with a shallow ridge waveguide structure common for both active and passive sections and formed in a single dry etching process, our process allows the fabrication of the monolithic photonic integrated circuit chip in a much simplified process. The fabricated device demonstrated multichannel mode-locking operation at a repetition frequency of 4.1 GHz in a fundamental mode-locking regime under both passive mode-locking and synchronous hybrid mode-locking conditions. Timing jitter as low as 1 ps was obtained, and preliminary pulse chirping characteristics were analyzed by a frequency-resolved optical gating technique. The exhibited performance makes our device a promising candidate as a multichannel ultrashort pulse optical source for future cost-effective high-speed optical networking and signal processing applications.